2021
DOI: 10.3390/nu13103334
|View full text |Cite
|
Sign up to set email alerts
|

Pathway Preferential Estrogens Prevent Hepatosteatosis Due to Ovariectomy and High-Fat Diets

Abstract: About 20–30% of premenopausal women have metabolic syndrome, and the number is almost double in postmenopausal women, and these women have an increased risk of hepatosteatosis. Postmenopausal women with metabolic syndrome are often treated with hormone replacement therapy (HRT), but estrogens in currently available HRTs increase the risk of breast and endometrial cancers and Cardiovascular Disease. Therefore, there is a critical need to find safer alternatives to HRT to improve postmenopausal metabolic health.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(38 reference statements)
2
2
0
Order By: Relevance
“…Since the activation of mERα in the medial preoptic area appeared to decrease overnight food and water intake in ovariectomized female rats, mERs have been postulated to control ingestive behaviors that occur at least in part through interactions with mGluR [ 134 ]. This is in line with PaPE-1-induced activation of mERα/mERβ, which reduced body weight gain and fat accumulation in the adipose tissues (perigonadal, perirenal, and subcutaneous) of ovariectomized mice [ 98 ] and significantly decreased liver weight and lipid accumulation in diet-induced obesity or leptin-deficient obese mice [ 135 ]. In these last two models, PaPE-1 also lowered the expression of genes associated with fatty acid metabolism and collagen deposition [ 98 , 135 ].…”
Section: Metabolic Effects and Vascular Protectionsupporting
confidence: 63%
See 1 more Smart Citation
“…Since the activation of mERα in the medial preoptic area appeared to decrease overnight food and water intake in ovariectomized female rats, mERs have been postulated to control ingestive behaviors that occur at least in part through interactions with mGluR [ 134 ]. This is in line with PaPE-1-induced activation of mERα/mERβ, which reduced body weight gain and fat accumulation in the adipose tissues (perigonadal, perirenal, and subcutaneous) of ovariectomized mice [ 98 ] and significantly decreased liver weight and lipid accumulation in diet-induced obesity or leptin-deficient obese mice [ 135 ]. In these last two models, PaPE-1 also lowered the expression of genes associated with fatty acid metabolism and collagen deposition [ 98 , 135 ].…”
Section: Metabolic Effects and Vascular Protectionsupporting
confidence: 63%
“…This is in line with PaPE-1-induced activation of mERα/mERβ, which reduced body weight gain and fat accumulation in the adipose tissues (perigonadal, perirenal, and subcutaneous) of ovariectomized mice [ 98 ] and significantly decreased liver weight and lipid accumulation in diet-induced obesity or leptin-deficient obese mice [ 135 ]. In these last two models, PaPE-1 also lowered the expression of genes associated with fatty acid metabolism and collagen deposition [ 98 , 135 ]. Moreover, it has been shown that the activation of mERα along with the PI3K/Akt pathway enhances the anorectic action of apolipoprotein A-IV (apoA-IV), as evidenced by significantly increased Akt phosphorylation in response to E2-BSA [ 136 ].…”
Section: Metabolic Effects and Vascular Protectionsupporting
confidence: 63%
“…The signaling process between E 2 and downstream molecules is unknown. Pathway preferential estrogen 1 (PaPE-1) is a novel estrogen receptor ligand that has been shown to favorably affect metabolic functions [41]. Estrogen-related receptor alpha (ERRα) was reported to contribute to the sex disparity in NAFLD development by regulating hepatic triglyceride biosynthesis and VLDL assembly and secretion, providing a novel treatment target [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Purified HFDs for our studies (F3282 diet, Bio-Serv, USA), meant to mimic the "Western diet", are high in butterfat (~42% Kcal from fat) and polysaccharide. This diet is commonly used in metabolic syndrome studies [28,32,33].…”
Section: In Vivo Prostate Cancer Xenograft Modelmentioning
confidence: 99%